Effect of bovine colostrum on the cytokine profile in periodontal diseases. - Maria Serdyńska; Agata Poniewierska-Baran; Karol Serwin; Paulina Warias; Tomasz Sroczyński; Andrzej Pawlik (Polish Pharmaceutical Society, 2022)
ABSTRACT Subject of study Colostrum is a special type of secretion produced by the mammary glands of mammals only for the first few days after birth. It is a rich source of nutrients and components supporting the immune system. Colostrum is considered to be one of the strongest natural immunostimulants, which contains immunologically active factors and antibodies (especially IgA) responsible for passive immunity. The colostrum also includes immunomodulatory components, including lactoferrin (LF), α-lactalbumin, lysozyme, lactoperoxidase and proline-rich polypeptide (PRP). Colostrum is capable to modify the functioning of the immune system by regulating the secretion of inflammatory mediators. Aim of study The aim of the study was to determine the effect of bovine colostrum on the expression of inflammatory mediators by gingival cells in response to lipopolysaccharides (LPS) or lipopolysaccharides and colostrum stimulation. Material and methods To evaluate the effect of colostrum on periodontal disease, a culture model of cells isolated from the gingiva of a patient with periodontal disease was used. In cultures of gingival cells isolated from a patient with periodontal disease, the effect of colostrum on the expression of selected cytokines involved in the inflammatory process was assessed. such as IL1β, IL6, IL10, IL15, IL23A, and the activity of IL21R, TNFR1 and TNFR2 receptors. Gum cell cultures from a patient with periodontal disease was stimulated with lipopolysaccharides (LPS), and then 5% bovine colostrum was added. The control was gingival cells stimulated only by lipopolysaccharides, without the addition of colostrum, then the expression of selected cytokines was assessed on the mRNA level. Results Preliminary results suggest that bovine colostrum affect the expression of cytokines IL1β, IL6, IL10, IL15, IL23A, and the activity of IL21R, TNFR1 and TNFR2 receptors in lipopolysaccharides -stimulated gingival cell cultures. Conclusions The presented results indicate that bovine colostrum is of significant immunological importance not only for newborns for whom it is a wholesome food, but also for adults, as it supports the prevention and treatment of many diseases, including the treatment of periodontal diseases.